Optimization of TikTok Use as a Medium for Digital Literacy-Based Learning Outcomes in Elementary Schools - Kurniawan, Diki; Heryani, Rina; Agustin, Mubiar (International Conference on Elementary Education, 2025)
This study investigates the use of TikTok as a tool to enhance digital literacy in elementary school students. Using a one-group posttest-only design and incorporating the RADEC (Read, Answer, Discuss, Explain, Create) model, the research explored how students transformed their understanding of the topic "Changes in the State of Matter" into creative video content. The study found that TikToksignificantly improved students' understanding, retention, and engagement with the material, while also increasing their motivation and confidence. The structured learning process, guided by the RADEC model, integrated critical thinking and creativity, supporting the development of digital literacy skills. By creating and sharing TikTok videos, students were able to actively engage with the content in ways that traditional methods might not support. The findings suggest that TikTok can be a highly effective educational tool in primary education when used responsibly. This research highlights TikTok’s potential as an innovative educational tool that can enhance engagement and support digital literacy in elementary education